A construção do indígena como sujeito político: a luta dos Kaingang por terra e por reconhecimento em Faxinalzinho, RS - Almeida, Samara Peres Dornelles (2016)
The northern Rio Grande do Sul is marked by conflicts involving indigenous and family farmers, heritage of its colonization process which allocated areas of indigenous occupation to property of immigrants who arrived in this region in the early twentieth century. Taking this into consideration, this study had as its starting point a conflict occurred in 2014, involving Kaingang indigenous from Votouro Kandoia and family farmers in the city of Faxinalzinho in northern Rio Grande do Sul. These Kaingang indigenous have been camped for more than a decade in an area surrounded by farmers' houses and crops, claiming their lands of traditional occupation supported in their right to land guaranteed by the Federal Constitution of 1988. Opposing to these peoples' traditional rights, the family farmers declare themselves owners of the lands for possessing the title of purchase. In order to think about the strengthening of the Indigenous Movement, it was resorted, especially, to the theoretical contributions of Axel Honneth on the struggle for recognition regarding the compensation for the damage suffered by the moral disrespect in the spheres of law and social esteem. It is highlighted, however, that in addition to the violence suffered in the body, such as abuse, torture and mutilations, the Timeframe and the Proposed Amendment to the Constitution - PEC 215 seek to void the right conquered by the indigenous tangent to the demarcation of their traditional lands. Before the evolution of the Indigenous Movement, it was presented as objective of this study, to understand how the Kaingang indigenous from Votouro Kandoia are constructed as political subjects in the struggle for land and moral recognition. The methodologies used proceeded from secondary sources such as bibliographic consultations made from research concerning the same subject, document and content analysis in anthropological and historical reports, as well as, primary sources from interviews with indigenous and their regional and state leaders, representatives of indigenous organization, family farmers and union representatives linked to family farming. From the material obtained from these sources, five categories were considered, subalternity, undercitizenship, disqualification, depreciation and stigma, in order to analyze the indigenous struggle in question.